2021
DOI: 10.1016/j.jadohealth.2020.07.036
|View full text |Cite
|
Sign up to set email alerts
|

Three Decades of Research: The Case for Comprehensive Sex Education

Abstract: School-based sex education plays a vital role in the sexual health and well-being of young people. Little is known, however, about the effectiveness of efforts beyond pregnancy and sexually transmitted disease prevention. The authors conducted a systematic literature review of three decades of research on school-based programs to find evidence for the effectiveness of comprehensive sex education. Methods: Researchers searched the ERIC, PsycINFO, and MEDLINE. The research team identified papers meeting the syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
196
0
13

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 343 publications
(302 citation statements)
references
References 105 publications
6
196
0
13
Order By: Relevance
“…The use of a critical pedagogical framework may be an avenue to address this gap while also bridging existing bodies of research, including previous SHE calls for inclusion of pleasure [40,41] and a broader range of sexual health topics that extend beyond a focus on reducing risk [42]. While the potential value of critical pedagogy in SHE has not been widely discussed, it has been mentioned by some [4,43] and this study further supports this call. Furthermore, the handful of SHE studies that have incorporated student experiences, align with findings reported here, including the need for content that is more relevant to students' own lives, the elimination of the stigmatization of LGBTQ+ identities, and the use of strategies that welcome questions and promote dialogue [44].…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The use of a critical pedagogical framework may be an avenue to address this gap while also bridging existing bodies of research, including previous SHE calls for inclusion of pleasure [40,41] and a broader range of sexual health topics that extend beyond a focus on reducing risk [42]. While the potential value of critical pedagogy in SHE has not been widely discussed, it has been mentioned by some [4,43] and this study further supports this call. Furthermore, the handful of SHE studies that have incorporated student experiences, align with findings reported here, including the need for content that is more relevant to students' own lives, the elimination of the stigmatization of LGBTQ+ identities, and the use of strategies that welcome questions and promote dialogue [44].…”
Section: Discussionsupporting
confidence: 65%
“…Many such programs are also intended to be LGBTQ+ inclusive [1][2][3]. Comprehensive SHE programs are being adopted in response to strong evidence of their effectiveness [2] as well as in light of persistent health inequities, particularly in communities of color, and particularly among students identifying as LGBTQ+ [4][5][6]. Chicago Public Schools' (CPS) 2013 policy and accompanying curriculum is one such example [7].…”
Section: Introductionmentioning
confidence: 99%
“…Ten studies (50%) dealt with school-based interventions [ 45 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ], 9 (45%) referred to online interventions [ 46 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ] and 1 (5%) was a review of blended learning programs [ 64 ]. In total 491 studies were included in the 20 reviews covered by the present RoR.…”
Section: Resultsmentioning
confidence: 99%
“…All studies were conducted in high-income economies following the World Bank classification [ 65 ], including US samples in 16 of the 20 studies, although there are two studies in which the country of the sample is not identified [ 51 , 52 ]. Most of the studies evaluating interventions in school settings also include developing countries (low- and middle-income economies) [ 45 , 47 , 50 , 52 , 53 , 55 ], as is also the case in three reviews of online interventions [ 46 , 61 , 62 ] (see Table A2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation